Efficient Booleans algorithms for triangulated meshes of geometric modeling. Issue 4 (3rd July 2016) - Jiang, Xiaotong; Peng, Qingjin; Cheng, Xiaosheng; Dai, Ning; Cheng, Cheng; Li, Dawei
ABSTRACT: Boolean operation of geometric models is an essential element in computational geometry. An efficient approach is developed in this research to perform Boolean operation for triangulated meshes represented by B-rep. This approach is much fast and robust than many existing methods. The Octree technique is adapted to facilitate the division of the common space of two meshes in order to reduce the time of Octree's construction and intersection detection. Floating point arithmetic errors and singularity of intersections are then analyzed to guarantee the unique intersection between a segment and a face, and the continuity of intersections. A novel technique based on intersecting triangles is finally proposed to create required sub-meshes based on the type of Boolean operations. Some experimental results and comparisons with other methods are presented to prove that the proposed method is fast and robust. GRAPHICAL ABSTRACT: